Synthesis and antifungal activity of 1,2,3-triazole containing fluconazole analogues - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Kumar, Awanit; Shukla, Praveen K.; Sharma, Aanchal; Bhat, Manoj K. (Bioorganic & Medicinal Chemistry Letters, 2009)
Fluconazole based novel mimics containing 1,2,3-triazole were designed and synthesized as antifungal agents. Their antifungal activities were evaluated in vitro by measuring the minimal inhibitory concentrations (MICs). Compounds 12, 15, and 16 were found to be more potent against Candida fungal pathogens than control drugs fluconazole and amphotericin B. The studies presented here provide structural modi. cation of fluconazole to give 1,2,3-trazole containing molecules. Furthermore, these molecules were evaluated in vivo against Candida albicans intravenous challenge in Swiss mice and antiproliferative activities were tested against human hepatocellular carcinoma Hep3B and human epithelial carcinoma A431. It was found that compound 12 resulted in 97.4% reduction in fungal load in mice and did not show any profound proliferative effect at lower dose (0.001 mg/ml). (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Conjugates; Fluconazole

Fluconazole analogues containing 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moieties, a novel class of anti-Candida agents - Borate, Hanumant B.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Chandavarkar, Mohan A.; Vaiude, Sharangi R.; Joshi, Vinay A.; Wakharkar, Radhika D.; Iyer, Ramki; Kelkar, Ramesh G.; Chavan, Subhash P.; Kunte, Sunita S. (Bioorganic & Medicinal Chemistry Letters, 2010)
As a part of our program to develop new antifungal agents, a series of fluconazole analogues was designed and synthesized wherein one of the triazole moieties in fluconazole was replaced with 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moiety. The new chemical entities thus synthesized were screened against various fungi and it was observed that the compounds 4a and 4i are potent inhibitors of Candida strains. The structure-activity relationship for these compounds is discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Benzothiazinone; Benzoxazinone; Fluconazole

Novel hybrids of fluconazole and furanones: design, synthesis and antifungal activity - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Chavan, Subhash P.; Chandavarkar, Mohan A.; Iyer, Ramki; Tawte, Amit; Rao, Deepali; Deore, Jaydeep V.; Kudale, Ananada S.; Mahajan, Pankaj S.; Kangire, Gopinath S. (Bioorganic & Medicinal Chemistry Letters, 2011)
During our efforts to develop new antifungal agents, a number of hybrid molecules containing furanones and fluconazole pharmacophores were designed and synthesized. The new chemical entities thus synthesized were tested for their potential as antifungal agents against various fungal strains and it was observed that the compounds with general structure 7 were potent inhibitors of Candida albicans ATCC 24433, Candida glabrata ATCC 90030, Candida tropicalis ATCC 750 and Candida neoformans ATCC 34664 while the fluconazole analogues 12 exhibited antifungal activity against Candida albicans ATCC 24433 and Candida glabrata ATCC 90030. The structure-activity relationship for these compounds is discussed. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures to obtain molecules suitable for development as antifungal drugs. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; Fluconazole; Furanones